PERBANDINGAN KESEHATAN MENTAL ANTARA SISWA ATLET FUTSAL DAN SISWA REGULER PADA PEMBELAJARAN PJOK DI SMAN 10 BANDUNG - Sofyan Fikri Anggani, - (2022)
This study aims to determine whether there is a comparison of mental health between futsal athlete students and regular students in PJOK learning at SMAN 10 Bandung. The method used is a descriptive method. The population in this study were grade 10,11,12 students of SMAN 10 Bandung, while the samples were 50 futsal athlete students and 50 regular students. In taking samples, researchers used a total sampling technique. This study used an instrument in the form of a mental health measuring test questionnaire. Comparison of Student Mental Health Athletes futsal and Regular Students have a significant difference. The mental health of futsal athlete students at SMAN 10 Bandung is included in the low category in terms of overall scores because the daily activities of students at the school are seen from all aspects of the indicators, they always do morning and evening exercises, causing some of these students to be tired and unable to excited when participating in PJOK learning. The mental health of regular students at SMAN 10 Bandung is in the low category in terms of overall scores because students at the school, seen from all aspects of the indicators, feel less confident when they take part in PJOK learning and when they are appointed by the teacher to carry out new movements they feel anxious.